Prospective evaluation of tracheobronchial foreign bodies - A. T., Ihsan; Ambooken, Divya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Foreign body aspiration is a condition that requires immediate and prompt management to avoid complications. Aim of this study was to find out proportion of tracheobronchial foreign bodies in under five age group, common sites of foreign body lodgement, types of tracheobronchial foreign bodies, and complications associated with this. Methods: This study was conducted in Department of ENT at Jubilee Mission Medical College and RI, Thrissur, during the period of January 2018 to June 2019 and comprises 24 cases. Rigid bronchoscopy under general anesthesia was done to remove these foreign bodies. Results: Eighteen cases were in under 5 age group. Peanut was the most common foreign body aspirated followed by badam and vegetable seeds. Common site of lodgement was in bronchi with 10 cases in right bronchi and 9 cases in left bronchi. Complication seen associated with this was pneumonia in this study. Conclusions: Foreign body aspiration is common in young children and hence a positive history might be absent. Hence there is high chance of misdiagnosis and complications. Parent education is must and avoid giving ungrinded nuts to young children.